Prevalence and etiology of dentoalveolar trauma in 1,592 United States military working dogs: A 1-year retrospective study - Bilyard, Karin R.; Mullaney, Sara B.; Henry, Travis J. (Frontiers in Veterinary Science, 2023)
The objective of this study was to quantify the overall prevalence and classification of traumatic dentoalveolar injury (TDI) in a large population of Military Working Dogs (MWDs). The medical records of 1,592 MWDs undergoing routine oral exam and periodontal treatment over a 1-year period were reviewed. The MWDs were located at over 100 military veterinary treatment facilities across the globe. Patient signalment, occupational duty certification, tooth injured, and trauma etiology were recorded. The overall prevalence of TDI was 43.6%. The mean number of TDI per MWD was 1.2. Maxillary tooth fractures were the most common at 60.9% compared to mandibular tooth fractures 39.1%. The most common TDI was enamel-dentin-pulp fractures which accounted for 59.9% of all injuries. Incidental findings with an unknown cause accounted for the majority of tooth trauma 69.2% followed by housing 18.2%, bite work 6.2%, and blunt force trauma 6.0%. The frequency of TDI in the MWD population is substantial, with more than one out of every four MWDs requiring treatment. The probability of a tooth injury in the MWD population is nearly double compared to the pet dog population. Tooth type and age are significant predictors of severe tooth trauma requiring treatment. Improved understanding of MWD tooth trauma prevalence and risk factors can help drive change while maintaining deployment readiness of the team.